МАҚОЛЛАРДА ҚИЁСЛАШ, ЗИДЛАШ МУНОСАБАТИНИ ИФОДАЛАШДА СОНЛАРНИНГ АҲАМИЯТИ (Scientific journal of the Fergana State University, 2023)
In this article the importanсe of numbers in expressing the meaning of comparison and contrast  in using of uzbek people’s proverbs is analyzed.